Evaluation of biochemical factors influencing endurance performance in weightlifters - Ziyamuxammedova Saboxat Abdullaevna; Bokieva Gulnoza Xabibullaevna; Berdieva Dilnavoz Toshkanovna (Genius Journals, 2023)
In this analytical article, we considered the possibility of assessing the functional state and adaptive capabilities of combat athletes by measuring the dynamics of the difference in infraslow potentials of the brain (omega potentials). The presented method indirectly characterizes changes in the level of psychological tension and physical activity, which is relevant in martial arts, where the athlete is under high mental stress with a lack of space and time.
Keywords: infraslow potentials of the brain; omega potentials; adaptive capabilities; functional state